2021
DOI: 10.1111/ecog.05723
|View full text |Cite
|
Sign up to set email alerts
|

β diversity among ant communities on fragmented habitat islands: the roles of species trait, phylogeny and abundance

Abstract: Habitat loss and fragmentation reduce biodiversity and alter species composition in local communities. β diversity describes the variation in species composition between or among communities in fragmented landscapes and has two components: species turnover and nestedness. In this study, we assessed β diversity of ant assemblages on 24 island fragments in the Thousand Island Lake, China. We constructed a species‐level phylogenetic tree and measured five morphological traits of all ant species captured. We then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 74 publications
(119 reference statements)
5
19
0
Order By: Relevance
“…We further partitioned the functional beta diversity to disentangle the potential mechanisms of functional homogenization. We found shrubs decreased the functional richness difference component, which suggested that the functional homogenization is often linked to deterministic processes of environmental filtering (Si et al, 2016;Zhao et al, 2021). Shrubs functioning as habitats for nematode communities can limit the range of potential colonizers by favoring species with particular functional attributes (Cao et al, 2016;Lanta et al, 2018).…”
Section: Shrub Effects On the Functional Beta Diversity Of Nematodes ...mentioning
confidence: 77%
“…We further partitioned the functional beta diversity to disentangle the potential mechanisms of functional homogenization. We found shrubs decreased the functional richness difference component, which suggested that the functional homogenization is often linked to deterministic processes of environmental filtering (Si et al, 2016;Zhao et al, 2021). Shrubs functioning as habitats for nematode communities can limit the range of potential colonizers by favoring species with particular functional attributes (Cao et al, 2016;Lanta et al, 2018).…”
Section: Shrub Effects On the Functional Beta Diversity Of Nematodes ...mentioning
confidence: 77%
“…However, in practice, it is nearly impossible to protect all the streams in the whole region, owing to the limited resources. Under such circumstance, it is advisable to give higher conservation priorities to the sites and species that are more unique in a given region (Zhao et al, 2021). The decomposition of beta diversity into species or local contributions (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…90%) are dominated by Masson pine ( Pinus massoniana ) in the canopy, with many native fleshy-fruited plants in the sub-canopy and understory, including abundant shrubs such as Vaccinium carlesii , Eurya muricate and Lindera glauca [34]. This region has a typical subtropical monsoon climate with marked seasonality (hot and humid summers, and cool to mild winters) [36]. We monitored plant–frugivore interactions in this artificial island archipelago since 2019 [37].…”
Section: Methodsmentioning
confidence: 99%